2020
DOI: 10.1007/s13197-020-04244-5
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics metabolism by gut-isolated probiotics

Abstract: There are numerous species of bacteria resides in the lumen of human colon. The word 'colon', resembles colony or the colonization of microbiota of which plays an important role in the fermentation of prebiotics. The standpoint of prebiotic nowadays is well reported for attenuating gut dysbiosis in many clinical studies tested on animals and human. However, because of the huge amount of gut microbiome, the attempt to connect the dots between bacterial population and the host are not plainly discernible. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 135 publications
0
18
0
2
Order By: Relevance
“…Prebiotics have also been found to act as decoy receptors to inhibit the adhesion of some pathogenic bacteria to the intestine as reviewed by Hickey (2012) . Furthermore, the butyrate-producing strains in Firmicutes families Lanchnospiraceae and Ruminococcaceae were shown different growth profiles in the presence of FOS, GOS, and xylo-oligosaccharides (XOS) ( Rawi et al., 2020 ; Scott et al., 2020 ). Moreover, colonic fermentation can modulate the gut microbial population, such as the increase in bifidobacteria and lactobacilli in the GIT.…”
Section: Prebiotics and Their Mechanisms Of Actionmentioning
confidence: 99%
“…Prebiotics have also been found to act as decoy receptors to inhibit the adhesion of some pathogenic bacteria to the intestine as reviewed by Hickey (2012) . Furthermore, the butyrate-producing strains in Firmicutes families Lanchnospiraceae and Ruminococcaceae were shown different growth profiles in the presence of FOS, GOS, and xylo-oligosaccharides (XOS) ( Rawi et al., 2020 ; Scott et al., 2020 ). Moreover, colonic fermentation can modulate the gut microbial population, such as the increase in bifidobacteria and lactobacilli in the GIT.…”
Section: Prebiotics and Their Mechanisms Of Actionmentioning
confidence: 99%
“…The most recent definition of prebiotics is ‘a substrate that is selectively utilised by host microorganisms, conferring a health benefit’ 41 , and numerous studies on prebiotics have found health benefits not only for the gut but also for the host in general 31 , 42 . Most traditional prebiotics increase the number of specific bacteria, such as Lactobacillus and Bifidobacterium 31 . In addition, they selectively increase the abundance at the bacterial genus level; few studies have reported on prebiotics that selectively increase abundance at the bacterial species level.…”
Section: Discussionmentioning
confidence: 99%
“…YM is a polysaccharide that is digested and utilised by B. thetaiotaomicron, which metabolises it through a 'selfish mechanism' due its unique property of having three mannan-specific PULs; most other bacteria do not have such PULs and therefore cannot utilise it 7 . Unlike traditional prebiotics such as inulin, fructo-oligosaccharides, and galacto-oligosaccharides which increase Lactobacillus and Bifidobacterium 31 , we consider YM to be a valuable ingredient as a novel prebiotic candidate that increases the abundances of B. thetaiotaomicron and other Bacteroides spp. YM utilisation by B. thetaiotaomicron has been investigated in monoculture, co-culture, and gnotobiotic mice 7 , and our previous study showed that YM increases the abundance of B. thetaiotaomicron in in vitro rat faeces fermentation 32 .…”
mentioning
confidence: 99%
“…En la Figura 2 se observa que el tamaño de la vellosidad intestinal del tratamiento T3 y T2 fueron las de mayor longitud, teniendo una respuesta lineal sobre T0 de 9,2% y 38,9% respectivamente, tamaños que mejoran la morfometría con la inclusión de alimentos funcionales en caso de pollo y cuy según (Roa et al, 2018), los cerdos de traspatio tienen mayor resistencia a enfermedades intestinales, basados en la salud de su flora intestinal. En busca de alimentos funcionales, se incorporan bacterias o productos bacterianos a la alimentación (Quintero, 2018), que interfieran favorablemente haciéndola más eficiente, conocido como alimento eubiótico, probablemente por acción, de bacterias benéficas, ácidos orgánicos y enzimas a nivel intestinal (Rawi et al, 2020;Xiang et al, 2019), como los que aporta con el EB, influyendo en la fisiología del animal. El tamaño de las vellosidades intestinales determina la eficiencia de esta interacción, la cual se demuestra ya que mejorar la absorción de nutrientes (Rawi et al, 2020), en el yeyuno también se instalan las bacterias benéficas que estimulan el crecimiento de las vellosidades intestinales, disminuyendo la carga bacteriana patógena, lo que es un indicador de la salud del animal (Roa et al, 2018).…”
Section: De Las Vellosidades Intestinalesunclassified
“…En busca de alimentos funcionales, se incorporan bacterias o productos bacterianos a la alimentación (Quintero, 2018), que interfieran favorablemente haciéndola más eficiente, conocido como alimento eubiótico, probablemente por acción, de bacterias benéficas, ácidos orgánicos y enzimas a nivel intestinal (Rawi et al, 2020;Xiang et al, 2019), como los que aporta con el EB, influyendo en la fisiología del animal. El tamaño de las vellosidades intestinales determina la eficiencia de esta interacción, la cual se demuestra ya que mejorar la absorción de nutrientes (Rawi et al, 2020), en el yeyuno también se instalan las bacterias benéficas que estimulan el crecimiento de las vellosidades intestinales, disminuyendo la carga bacteriana patógena, lo que es un indicador de la salud del animal (Roa et al, 2018). Esto se traduce en la alimentación en el aprovechamiento eficiente del alimento, reduciendo el consumo sin afectar su crecimiento y producción.…”
Section: De Las Vellosidades Intestinalesunclassified